Analyse-diagnostic et performances de 5 perimetres irrigues autour de barrages au Burkina Faso: Rapport final - Tome 1 du Projet Management de l'Irrigation. Appendice II: Rapport sectoriel hydrauliqueAnalysis-diagnosis and performance of five reservoir-based irrigation schemes in Burkina Faso: Final report - Volume 1 of the Burkina Faso irrigation management project. Appendix II: Hydraulics sector report - International Irrigation Management Institute (International Irrigation Management Institute, 1996)
Synthesis report of the research results obtained under the Burkina Faso Irrigation Management Project between 1991-1997. This volume deals with hydraulics.